Menilik Peran Pengawasan Ketersediaan Bahan Pangan Pokok Di Kota Metro Perspektif Asas Food Security - Nandya, Putri Deva; Pertiwi, Nyimas Lidya Putri; Ningsih, Rahmah (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study examines the supervision of food availability in Metro City based on the principles of food security and good governance. Food availability comprising national reserves, domestic production, and imports when necessary is a key pillar of food security. Employing a descriptive qualitative approach, data were gathered through semi-structured interviews, documentation, field observation, and literature review. Informants included food distributors, vendors, and local government officials. The findings reveal that weak accountability, lack of transparency and public participation, as well as poor coordination and infrastructure, hinder effective supervision. The principle of good governance is seen as essential for ensuring fairness and responsiveness in food management, while food security emphasizes availability, accessibility, utilization, and supply stability. Recommended strategies include regulatory reform, human resource capacity development, institutional coordination improvement, and community involvement in participatory monitoring, to build a resilient and inclusive local food system.